Urgensi Upaya Preventif Dan Korektif Dalam Penanggulangan Tindak Pidana Perdagangan Orang Terhadap Wni Di Kamboja - Putra, Roni Alim; Etif, Etik; Sholikah, Dwi Imroatus (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
The phenomenon of Trafficking in Persons (TIP) targeting Indonesian citizens (WNI) in Cambodia in recent years highlights the vulnerability within the cross-border legal protection system for victims. These cases are predominantly orchestrated by international criminal syndicates utilizing online job scamming schemes, ensnaring hundreds of WNI into economic and psychological exploitation. This study aims to analyze the urgency of the Indonesian government's preventive and corrective measures in combating TIP against WNI in Cambodia, employing a national and international legal approach. The methodology used is normative legal research, incorporating statutory, conceptual, and case study approaches. The research findings indicate that the government's preventive efforts are still reactive and lack comprehensive integration. Conversely, corrective measures, particularly victim handling, have not been adequately balanced with sufficient recovery support (including psychological and legal rehabilitation). This study emphasizes the critical need for synergy between the Governments of Indonesia and Cambodia. Furthermore, harmonization of national laws with the Protocol to Prevent, Suppress and Punish Trafficking in Persons, Especially Women and Children (Palermo Protocol), is essential to strengthen the protection mechanism for WNI victims of TIP abroad.